Exposure to mercury and thyroid function: Is there a connection? - Marić, Djurdjica; Bonderović, Vera; Javorac, Dragana; Baralić, Katarina; Bulat, Zorica; Djukić-Ćosić, Danijela; Mandić-Rajčević, Stefan; Žarković, Miloš; Buha Djordjević, Aleksandra (Archives of Pharmacy, 2022)
Mercury (Hg) is one of the most important environmental pollutants with endocrine-disrupting properties. There is little data from epidemiological studies describing the dose-response relationship between toxic metal levels and hormone levels. The aim of this study was to use the nearest neighbor matching analysis to determine the difference in Hg concentration in healthy/sick subjects with thyroid disease and to use Benchmark modeling to determine the dose-response relationship between Hg levels in the blood and thyroid-stimulating hormone (TSH) and thyroid hormones in serum. Blood samples were collected and used for Hg measurement using the ICP-MS method, and separated serum was used for hormone analysis. The study showed the existence of a statistically significant difference in Hg levels measured in healthy and sick subjects and the existence of a dose-response relationship between Hg and all measured hormones, with a narrow interval obtained for the Hg-TSH pair. The results of this research support the use of the Benchmark dose approach for the purpose of analyzing data from human studies, and our further research will be focused on examining the impact of low doses on animal models in order to determine more precise effects of low doses on the organism.